Investigating the Implementation of Process Approach to the Teaching and Learning of Writing Skills: The Case of Ethiopian University - Zeleke, Yitayal Damtew (Institut Agama Islam Negeri Kudus, 2022)
The purpose of this study is to investigate the implementation of process approach to the teaching and learning of writing skills at one of Ethiopian University. The research employed descriptive research design with mixed approach to data gathering and analysis. While qualitative data were analyzed using thematic analysis the quantitative data were analyzed using a descriptive SPSS analysis. The subjects of the study were both 1st year 5 male and 15 female and 2nd year 5 male and 8 female totally 33 undergraduate English as a foreign language students and their 2 writing skills instructors. This was because 1st year undergraduate English as foreign language students take the writing course i.e. Basic Writing Skills and 2nd year undergraduate English as foreign language students take the writing course i.e. Advanced Writing Skills and they were selected by using comprehensive sampling technique. The researchers used classroom observation, questionnaires and semi-structured interview as instruments to collect relevant data. The results of the analysis showed that, instructors did not always focus on the process approach while they deliver the writing lessons and activities; instead they mainly use the product approach in conducting the lessons. There were also factors like, lack of additional material sources, the correction limitation of students’ written works and students’ inability to express themselves’ in the target language that hindered the implementation of the process approach of teaching writing skills.